VALUE-BASED HR MANAGEMENT IN THE PRODUCTION SEGMENT (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In order to improve organisational performance and employee engagement, this article examines the idea of value-based human resource (HR) management in the industrial sector. Production firms must embrace creative HR strategies that closely connect with their fundamental beliefs and goals as sectors change in response to globalisation, technological improvements, and shifting market needs. The values of value-based HR management are covered in the paper, along with ethical behaviour, stakeholder involvement, and an emphasis on how employees contribute to company values. The article illustrates how adopting a value-oriented strategy may result in increased productivity, better employee morale, and sustainable business practices using case studies and examples from top manufacturing companies.